Study on Bioallergens in Selected Areas of Visakhapatnam - Kiranmai Reddy, M.; Himavathi, G.; Manga, S. (Asian Journal of Chemistry, 2012)
The air consists of several bioallergens like spores of bacteria, fungi, organic dust and pollen grains, which can cause severe allergic reactions in humans. To estimate the bioallergens, a study of air micro flora was conducted in different locations in Visakhapatnam. The fungal density in the air varied from 0.9 × 101 to 4.3 × 103. In the present study 22 fungal species were reported. The most common fungi identified were Aspergillus, Cladosporium, Alternaria, Penicillum, Curvularia, Mucor and Rhizopus. Aspergillus strains were present in alarming levels followed by Cladosporium, Alternaria and Curvularia. Fungal spores are known to be potential aeroallergen and could well be a health hazard to all people travelling regularly in these areas.